2011
DOI: 10.1021/ef101522w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Island Structures as the Dominant Architecture of Asphaltenes

Abstract: Laser desorption laser ionization mass spectra of 23 model compounds and 2 petroleum asphaltene samples are presented. These experiments involved desorption by irradiation with the 10.6 μm output of a CO2 laser followed by single-photon ionization with the 157 nm output of a fluorine excimer laser. The average molecular weight of the asphaltene samples agrees closely with that found previously using multiphoton ionization with the 266 nm output of a Nd:YAG laser. The fragmentation behavior as a function of ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
313
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(339 citation statements)
references
References 24 publications
24
313
0
2
Order By: Relevance
“…Further, only few uses exist for asphaltenes, including 69 expensive upgrading to distillates [12], road construction [13] 70 and recently proposed use in organic electronic materials [14,15] [9] to be especially well suited for evaporation and ionization of 114 asphaltenes since it has no bias to more polar analytes and it pro-115 duces only one ion type, molecular ion (M +Å ), for all asphaltene 116 model compounds studied [9]. In addition, it has been demon-117 strated that laser desorption/laser ionization of analytes relevant 118 to asphaltenes produces molecular ions with minimal fragmenta-119 tion for the majority of analytes studied [33,34]. These methods 120 allow for the determination of the molecular weight and elemental 121 composition of all analytes present.…”
mentioning
confidence: 99%
“…Further, only few uses exist for asphaltenes, including 69 expensive upgrading to distillates [12], road construction [13] 70 and recently proposed use in organic electronic materials [14,15] [9] to be especially well suited for evaporation and ionization of 114 asphaltenes since it has no bias to more polar analytes and it pro-115 duces only one ion type, molecular ion (M +Å ), for all asphaltene 116 model compounds studied [9]. In addition, it has been demon-117 strated that laser desorption/laser ionization of analytes relevant 118 to asphaltenes produces molecular ions with minimal fragmenta-119 tion for the majority of analytes studied [33,34]. These methods 120 allow for the determination of the molecular weight and elemental 121 composition of all analytes present.…”
mentioning
confidence: 99%
“…For example, the proposed molecular weight and island molecular architecture have been strongly supported by L2MS studies [29]. Most importantly, L2MS studies have established the ability to disaggregate asphaltene nanoaggregates, [30] a known problem with some mass spectral techniques.…”
Section: Introductionmentioning
confidence: 94%
“…1, some bulk decomposition studies of asphaltenes indicate the presence of some molecular populations with two or perhaps more aromatic ring systems [45]. Perhaps this fraction is relatively small, thereby not impacting molecular (not bulk) decomposition measurements, which clearly indicate the dominance of island architecture [29]. In addition, in bulk decomposition studies, asphaltenes are found to form structures with two or more aromatic ring systems; [46] thus, interpretation of these decomposition studies in terms of virgin asphaltene molecular structure is rendered very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Essa característica é condizente com espectros encontrados em outros trabalhos para amostras de diferentes origens e obtidos por outros métodos da espectrometria de massas. 42,[49][50][51][52][53][54] As massas molares médias dos petróleos obtidas por LDI-MS foram 622 Da e 643 Da para os petróleos P01 e P02, respectivamente. As massas molares médias das frações resultantes das extrações com n-pentano (C5I/ C5S) foram sempre inferiores àquelas com n-heptano (C7I/ C7S): 592/ 579 Da para as frações C5 do P01 e 745/ 621 Da para as do P02 contra 759/ 615 Da para as frações C7 do P01 e 814/ 651 Da para as do P02.…”
Section: Massas Molares Médias De Petróleos E Frações Por Espectrometunclassified